THE ACCURACY INVESTIGATION OF THE HIGH POSITION OF THE ROAD COVERAGE SURFACE WITH THE DIFFERENT GEODESIC DEVICES’ APPLICATION - Y. V. Stolbov; S. V. Stolbova; L. A. Pronina; A. I. Uvarov (Вестник СибАДИ)
Introduction. The updated wording of the rulebooks SP apply instead of the SNiP for the road construction last time, in which the accuracy requirements of the device bases and pavements is greatly increased. To ensure high requirements to the accuracy of vertical position of the structural layers of bases and covers roads there is a need of application of modern surveying instruments (precision optical levels and electronic total stations with different accuracy). Materials and methods. The research of the vertical position accuracy (unevenness) of the coating roads surface in IV category at the constructive layers’ device is observed with the road vehicles without an automatic system of vertical heights and with the leveling step through 10 m. Results. The calculated statistical characteristics and parameters for the deviations’ distribution of the amplitudes on the pavements’ surface elevation, which are obtained according to the measurement results, are used on the N-3 optical level and on the TRIMBLE M3 electronic total station. Discussion and conclusion. The standard deviations’ values of the amplitude, which are obtained by the N-3 optical level’s usage and by the electronic total station’s usage, remain on the same accuracy order. Therefore, the usage of the electronic total stations for the accuracy ensuring is planned also on the vertical position of their bases and pavements.